Thermal and structural characterization of acrylonitrile butadiene styrene (ABS) copolymer blended with polytetrafluoroethylene (PTFE) particulate composite. (5th June 2019) - Mahesh Kumar, R; Rajini, N; Senthil Muthu Kumar, T; Mayandi, K; Siengchin, Suchart; Ismail, Sikiru O
Abstract: A novel thermally sustainable polymer composite was fabricated with Acrylonitrile Butadiene Styrene (ABS) as the matrix and Polytetrafluroethylene (PTFE) particle as the filler, using injection molding process with 10 and 20 wt% PTFE filler. The composites were characterized by Fourier transform infrared spectroscopy (FTIR), x-ray diffraction (XRD) and Thermogravimetric analysis (TGA). The composites were also tested for their visco-elastic properties using Dynamic mechanical analyzer (DMA). The ABS/PTFE composites exhibited high thermal stability and better visco-elastic properties than the ABS matrix. Consequently, this hybrid blended polymer can be a suitable alternative material for tribological applications in both automobile and aerospace industries, among others.